Efektivitas Strategi Hedging Menggunakan Kontrak Indeks Lq45 Futures dalam Meminimalisasi Risiko Sistematis Portofolio - Nadia Asandimitra Haryono; M. Riadhos Solichin (Universitas Negeri Surabaya, 2018)
AbstractInvestor can make hedging to the systematic risk or market risk by using LQ45 index futures contract whose value comparable to the share portfolio value they have. This research had the purpose to prove used the LQ45 index futures contract in minimize the portfolio systematic risk. In this research used LQ45 index as the proxy on the portfolio have been properly diversified. Data used in this research were LQ45 index daily value data and the daily closing price of LQ45 index futures with 2004-2005 research period. Testing was conducted by comparing the portfolio return hedged variance to the portfolio return unhedged variance. Calculation of hedging effectiveness used LQ45 index futures contract as much as -9%, negative hedging effectiveness calculation due to the portfolio return hedged variance larger than portfolio return unhedged variance or, in the other words the risk in the futures market was larger than the risk in the spot market. Thus, the LQ45 index futures contract was ineffective to use as the hedging strategy in minimize the portfolio systematic risk